1989
DOI: 10.1172/jci114359
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor enhances renal tubule cell regeneration and repair and accelerates the recovery of renal function in postischemic acute renal failure.

Abstract: To determine the timing and location of renal cell regeneration after ischemic injury to the kidney and to assess whether exogenous epidermal growth factor (EGF) enhances this regenerative repair process to accelerate recovery of renal function, experiments were undertaken in rats undergoing 30 min of bilateral renal artery clamp ischemia followed by reperfusion for varying time intervals. Renal cell regeneration, as reflected by incorporation of radiolabeled thymidine within the kidney, began between 24 to 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
202
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(212 citation statements)
references
References 29 publications
7
202
3
Order By: Relevance
“…For instance, the renal growth that follows unilateral nephrectomy is associated with increased renal EGF [11,10] and the associated tubular cell hyperplasia can be reduced by the administration of anti-EGF antibodies [28]. In acute tubular necrosis following ischaemic injury [29,30] or mercuric chloride toxicity exogenously administered EGF accelerates tubular regeneration and recovery. The factors responsible for increased EGF during early diabetes remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the renal growth that follows unilateral nephrectomy is associated with increased renal EGF [11,10] and the associated tubular cell hyperplasia can be reduced by the administration of anti-EGF antibodies [28]. In acute tubular necrosis following ischaemic injury [29,30] or mercuric chloride toxicity exogenously administered EGF accelerates tubular regeneration and recovery. The factors responsible for increased EGF during early diabetes remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that locally produced growth factors may serve as mediators of regeneration of renal epithelial cells following acute injuries (1,2,7). Specifically, previous studies have suggested that EGF, 1 or members of the EGF growth factor family, may play an important role in repair of renal injury (8,9). After either ischemic tubular injury or folic acid nephropathy, EGF receptor density increases (10 -12), and subcutaneous injection of EGF or TGF-␣ significantly accelerates [ 3 H]thymidine incorporation and recovery of epithelial cell function (8 -11, 13, 14).…”
mentioning
confidence: 99%
“…This finding indicates that EGF is involved in improving effects of protein restriction on renal failure. This notion is supported by reports that chronic renal failure caused by 5/6 nephrectomy is improved by extrinsic EGF [14] and that EGF accelerates regeneration of tubular cells and ameliorates renal failure [7].…”
Section: Discussionmentioning
confidence: 55%